The unsuccessful of Satu Data Indonesia (SDI) implementation: a lesson learned from local government - Ardhi Dwi Firmansyah; Tony Dwi Susanto (Institute of Computer Science (IOCS), 2023)
Data is a new asset in an organization. Data governance is needed for data to become a valuable asset. However, the implementation of data governance at the regional level, known as SDI has not been successful. SDI readiness score of 45.60%. Therefore, this study aims to identify problems and strategies related to the implementation of SDI at the regional level. Based on the results of an exploration of the implementation of SDI in the Madiun Regency Government, 24 problems were found. There are 3 problems in each aspect of SDI readiness. The eight aspects cover regulation, institutional, performance and conformance, management and utilization, technology, human resources, finance, and collaboration. To address these issues, eight strategies were proposed, including strengthening policies, increasing stakeholder commitment, formulating clear guidelines, raising awareness, facilitating infrastructure, developing employee skills, optimizing budget allocations, and promoting collaboration. These strategies aim to ensure successful SDI implementation in local government by improving data management, stakeholder involvement, resource allocation, and performance. Continuous improvement is important for long-term success.